Bringing Diversity Education to Life: The Impact of Learning Videos on Elementary School Students' Learning Outcomes - Rodiyana, Roni; Maftuh, Bunyamin; Sapriya, Sapriya; Syaodih, Ernawulan; Yanto, Ari; Sofyan, Davi (Utamax : Journal of Ultimate Research and Trends in Education, 2023)
This study examines the lack of comprehension among students regarding subject matter that is highly relevant to their daily lives, emphasising the importance of their understanding. The encounter with diverse situations outside the classroom is a common experience for students; however, the insufficient availability of learning tools, unappealing media, and inadequate utilisation of school facilities contribute to their limited understanding. To address this issue, learning films are proposed as an alternative media to enhance student engagement, serve as effective learning materials, and make use of school resources such as projectors. The aim of this research is to create and evaluate the effectiveness of instructional video media with a diversity theme in improving learning outcomes among class III elementary school students. The design and development (D&D) method, specifically the PPE development model, was utilised in this study, involving three stages: planning, development, and evaluation. The input of media experts, material experts, and learning experts was sought to assess the feasibility of the learning videos. The results indicated that the learning films received a feasibility rating of 95% in the "extremely feasible" category, affirming their suitability for educational settings. Experts predicted that the implementation of learning films could significantly enhance student learning outcomes. The methodology encompassed data collection through the D&D method, including planning and conducting evaluations by experts, as well as the subsequent analysis and interpretation of the results. Ultimately, this study aims to improve the actual learning outcomes of class III elementary school students through the utilisation of instructional video media with a diversity theme.